2013
DOI: 10.1103/physrevd.88.103002
|View full text |Cite
|
Sign up to set email alerts
|

Time delay between relativistic images as a probe of cosmic censorship

Abstract: We study the time delay between successive relativistic images in gravitational lensing as a possible discriminator between various collapse end states and hence as a probe of cosmic censorship. Specifically we consider both black hole and naked singularity spacetimes admitting photon spheres where an infinite number of relativistic Einstein Rings can be formed at almost the same radius and naked singularity spacetimes without a photon sphere where multiple relativistic Einstein Rings can form almost up to the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 36 publications
(66 reference statements)
0
25
0
Order By: Relevance
“…Finally, we will consider the time delays between the relativistic images, which is another important kind of observables in strong gravitational lensing [76][77][78][79][80]. From the null geodesics equation (12), one has…”
Section: Observable In Strong Gravitational Lensing and Time Delamentioning
confidence: 99%
“…Finally, we will consider the time delays between the relativistic images, which is another important kind of observables in strong gravitational lensing [76][77][78][79][80]. From the null geodesics equation (12), one has…”
Section: Observable In Strong Gravitational Lensing and Time Delamentioning
confidence: 99%
“…Virbhadra et al 1998, and for recent update and further references, Sahu et al, 2012, 2013. Assuming that a Kerr-like solution of Einstein equations with massless scalar field exists at the center of galaxies, its lensing properties are studied and it was found that there are effects due to the presence of both the rotation and scalar field that would affect the behavior of the bending angle of the light ray, thus making those objects observationally different from black holes (see e.g.…”
Section: Astrophysical and Observational Aspectsmentioning
confidence: 99%
“…Gravitational lensing attracts numerous attentions because of its extensive astronomical applications [1][2][3][4][5][6]. Within this geometrical effect, the gravitational time delay of electromagnetic waves acts as one of the most significant parts [7][8][9][10], and has been investigated in detail. The pioneering work of obtaining the first-order gravitational delay of radar echo signals was carried out by Shapiro [11] to test general relativity [12].…”
Section: Introductionmentioning
confidence: 99%